2023
DOI: 10.1051/e3sconf/202340105041
|View full text |Cite
|
Sign up to set email alerts
|

Measures of effective use of the capacity of twotrack sections of JSC “Uzbekistan Railways”

Abstract: The article first presents the analysis of the complete structure of all two-track sections of JSC “Uzbekistan Railways” with mixed traffic, and then the proposals of local and foreign scientists regarding the determination of the coefficient of displacement of freight trains from the graph on two-track sections in conditions of mixed traffic of trains are described in detail. In addition, the factors affecting the displacement coefficient of freight trains from the graph were analyzed, as well as the reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Turanov and other recognized scientists to determine the height of the sorting slide, it is calculated based on the most difficult conditions -winter temperature and headwind, and for a bad runner, a four-axle empty covered wagon is selected. The reason for choosing this car was that the cross-sectional area of the closed car is larger than that of other cars (Table 1) [4,6,8,10,12,14,16,18]. The following forces act on a car moving along an inclined plane (Fig.…”
Section: The Main Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Turanov and other recognized scientists to determine the height of the sorting slide, it is calculated based on the most difficult conditions -winter temperature and headwind, and for a bad runner, a four-axle empty covered wagon is selected. The reason for choosing this car was that the cross-sectional area of the closed car is larger than that of other cars (Table 1) [4,6,8,10,12,14,16,18]. The following forces act on a car moving along an inclined plane (Fig.…”
Section: The Main Partmentioning
confidence: 99%
“…Analyzing the content of the published discussions devoted to the problem of designing sorting slides [1][2][3][4][5][6][7][8][9][10], it can be concluded that until now the dynamics of the car moving along the profile of the sorting slide has not been studied enough. For this reason, it is worth noting the ideas about the importance of controlling, coordinating the speed of a moving car along the profile of a sorting slide.…”
Section: Introductionmentioning
confidence: 99%